Potential effective elements in combined lifestyle interventions for overweight children. (13th November 2019) - Saat, J J E H; Fransen, G A J; Naumann, E; van der Velden, K; Assendelft, W J J
Abstract: Background: Combined Lifestyle Interventions (CLIs), offered in primary care, aim to prevent childhood overweight/obesity. Combined means the intervention focuses on optimalising nutrition behaviour, physical activity and mental health, provided by a multidisciplinary team. Although the effectiveness of CLIs is still not clear, CLIs are already implemented in daily practice in the Netherlands. These CLIs are not uniformly designed and have variations in protocols to suit the needs of their community. Due to the many different CLIs it is difficult to investigate their effectiveness. To be able to investigate effectiveness of GLIs, we first need to unravel the 'black boxes' of CLIs and identify their (potential) effective elements. Methods: First, we carried out a literature study on elements that may contribute to the effectiveness of a GLI (the so called potential elements). Next, we organized an online brainstorm session, where experts such as researchers and paramedics could add or specify potential elements. We made all elements measurable, with help of experts. These elements were incorporated into a tool to check presence of potential elements in CLIs. This tool was tested on reliability by comparing the results of four researchers who assessed protocols of six CLIs. Results: 42 experts participated in the brainstorm session. The literature study and brainstorm session together resulted in 54 potential elements for CLIs for overweight/obese children, categorized in four themes: organization, content, role of parents and role of experts. For all six protocols, a minimum of 85% of the potential elements in the tool have been scored the same by the four assessors. Conclusions: We developed a reliable tool to determine potential effective elements in a CLI. In future studies, this tool can be used to identify specific elements that are effective in CLIs for overweight/obese children by comparing the tool with health effects of CLIs. Key messages: We were able to develop a reliable instrument to better analyze the factors that contribute to positive health effects of combined lifestyle interventions for children with overweight or obesity. the developed tool with potential effective elements must be filled in for more CLIs, where after we can find corresponding elements in the most effective CLIs.